Agribusiness in Argentina: Review of the Marcos Juárez case in the heart of the “pampa humeda” - Geremía, Daiana (Universidad Nacional de Villa María, 2019)
In this article we intend to contribute in the discussions and the study of the agribusiness model in Argentina and in particular, the description of a case study located in the heart of the Pampa Húmeda, Argentina. Understanding that we are living a consolidated and dominant stage of the extractive model in the so-called “third world” societies, where a fever of primary products with little processing recovers, due to growing international demand. This article proposes to think that the transformations produced by the new agribusiness model have been very complex, and have generated various plots and identities, especially when we look closely at soybean cities, where the productive and social fabric is closely linked to the operation of agriculture.